2011
DOI: 10.1111/j.1365-2230.2010.03999.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of topical 3% diclofenac sodium gel and 5% imiquimod cream for the treatment of actinic keratoses

Abstract: Although DFS and IMQ each had considerable efficacy in the treatment of AK, the efficacy of DFS seemed to decrease after cessation of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
3
24
0
1
Order By: Relevance
“…IMQ is a toll-like receptor agonist, which is used to treat condyloma acuminata, solar keratosis, basal cell carcinoma and other conditions [27, 28]. Van der Fits et al revealed that IMQ-induced psoriasis-like inflammation markedly reflected the characteristics of plaque type psoriasis, which include hyperproliferative keratinocyte, parakeratosis, absence of a granular layer, and existence of inflammatory cells consisting of T cells, neutrophils, DCs and vascular proliferation [23].…”
Section: Discussionmentioning
confidence: 99%
“…IMQ is a toll-like receptor agonist, which is used to treat condyloma acuminata, solar keratosis, basal cell carcinoma and other conditions [27, 28]. Van der Fits et al revealed that IMQ-induced psoriasis-like inflammation markedly reflected the characteristics of plaque type psoriasis, which include hyperproliferative keratinocyte, parakeratosis, absence of a granular layer, and existence of inflammatory cells consisting of T cells, neutrophils, DCs and vascular proliferation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, topical therapy has been proposed to reduce the potential gastrointestinal and cardiovascular side effects of conventional NSAIDs in the treatment of actinic keratosis (21), pain (22) and arthritis (23). The topical administration of P-S to mice bearing human skin cancer xenografts resulted in 4- to 5-fold lower levels of sulindac and its metabolites (<35 μM) compared to those after oral administration (>200 μM) (12).…”
Section: Discussionmentioning
confidence: 99%
“…conducted a study comparing the use of 3% diclofenac sodium and 5% imiquimod and found similar cure rates at the end of treatment in both groups, but with a higher rate of recurrence in the diclofenac sodium group 12 weeks after treatment completion. 23 …”
Section: Discussionmentioning
confidence: 99%